Clinical and Radiographic Features of the Autosomal Recessive form of Brachyolmia Caused by PAPSS2 Mutations - ELÇİOĞLU, HURİYE NURSEL (WILEY, 2013)
Brachyolmia is a heterogeneous skeletal dysplasia characterized by generalized platyspondyly without significant long-bone abnormalities. Based on the mode of inheritance and radiographic features, at least three types of brachyolmia have been postulated. We recently identified an autosomal recessive form of brachyolmia that is caused by loss-of-function mutations of PAPSS2, the gene encoding PAPS (3-phosphoadenosine 5-phosphosulfate) synthase 2. To understand brachyolmia caused by PAPSS2 mutations (PAPSS2-brachyolmia), we extended our PAPSS2 mutation analysis to 13 patients from 10 families and identified homozygous or compound heterozygous mutations in all. Nine different mutations were found: three splice donor-site mutations, three missense mutations, and three insertion or deletion mutations within coding regions. In vitro enzyme assays showed that the missense mutations were also loss-of-function mutations. Phenotypic characteristics of PAPSS2-brachyolmia include short-trunk short stature, normal intelligence and facies, spinal deformity, and broad proximal interphalangeal joints. Radiographic features include platyspondyly with rectangular vertebral bodies and irregular end plates, broad ilia, metaphyseal changes of the proximal femur, including short femoral neck and striation, and dysplasia of the short tubular bones. PAPSS2-brachyolmia includes phenotypes of the conventional clinical concept of brachyolmia, the Hobaek and Toledo types, and is associated with abnormal androgen metabolism. (C) 2013 Wiley Periodicals, Inc.
Keywords: brachyolmia; PAPSS2; phenotype; androgen excess; 3-PHOSPHOADENOSINE 5-PHOSPHOSULFATE SYNTHESIS; BRACHYMORPHIC MICE; DEFECT; DYSPLASIA; EXPRESSION; SYNTHASE